Dendritic nanoparticle self-assembly from drying a sessile nanofluid droplet - Ren, Junheng (2022)
The pattern formation left by a drying nanofluid droplet is related to the evaporation induced particle self-assembly. The experimental results demonstrate the formation of dendritic particle deposition after the liquid phase of unpinned sessile nanofluid droplets is fully evaporated. The dried-in particle assemblies exhibit the dendritic patterns connecting the sprawling branches with a central core structure. The branched structures are formed by particles merging in the receding front. A three-dimensional lattice-gas kinetic Monte Carlo model is developed to simulate the particle self-assembling behaviour in a drying particle-laden droplet with the dewetting three-phase line. The parameter study is carried out to demonstrate the trend of the dendritic pattern formation. The various patterns are simulated by varying the chemical potentials and the interaction energies among particles, liquids, and substrates. The dendritic particle depositions are measured in three dimensions after the nanofluid droplet is completely dried. Qualitative agreement is observed between the experimental and the numerical results. Thicker branches and larger central cores are observed with an increase of particle concentrations.